Biosynthesis of ZnO Nanoparticles by Adansonia Digitata Leaves Dye Extract: Structural and Physical Properties. (6th March 2018) - Kane, A. O.; Ngom, B.D.; Sakho, O.; Zongo, S.; Ndiaye, N.M.; Ndlangamandla, C.L.; Manyala, N.; Maaza, M.
ABSTRACT: This work reports on the synthesis and the main physical and chemical properties of ZnO nanoparticles synthesized by an entirely green Bio-physical-chemical process using natural dye extract from Adansonia digitata leaves as an efficient reduction/oxidizing agent. Their structural and surfaces properties by electron microscopy, X-rays diffraction, Raman and TGA, as well as gas adsorption analysis are reported.